Antioxidant Flavonoid Glycoside from Leaves of Cacao Mistletoe (Scurrula ferruginea (Jack) Danser) - Mai Efdi; Dara Pratama; Afrizal Itam; Tia Okselni (Universitas Gadjah Mada)
Scurrula ferruginea (Jack) Danser is a folk medicine to treat several diseases. S. ferruginea is the mistletoe that lives by deriving nutrients from the host. Hence, the host has a significant effect on the biological activities and bioactive components of S. ferruginea. In this study, the leaves of S. ferruginea were macerated by methanol solvent to extract the chemical components and fractionated by hexane and ethyl acetate solvent, respectively, to separate organic compounds. The biological activity of crude extracts as the antioxidant was investigated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The result showed that the highest antioxidant activity was obtained from the ethyl acetate fraction with the IC50 of 10.88 ± 0.39 µg/mL. Furthermore, the trituration method used several solvents to isolate secondary metabolites from the initial crude methanol extract. This purification process produced a flavonoid compound of quercitrin. The antioxidant activity of quercitrin was also determined by the DPPH method. The result showed that this compound has stronger activity than the crude extracts with the IC50 of 5.95 ± 0.11 µg/mL. This study demonstrated that cacao mistletoe of S. ferruginea may have the potential activity to treat the diseases caused by the presence of free radicals.